VD_FINDINFO Jug / 2012 / 246 vom 26. März 2012 - VD Tribunal cantonal (2012)
ASSASSINAT, TENTATIVEDROIT PÉNAL, LÉSION CORPORELLE SIMPLE, TRANSACTIONACCORD | 123 ch. 1 CP, 181 CP, 183 ch. 1 CP, 22 ad 112 CP